Faktor – Faktor Yang Mempengaruhi Depresi Postpartum pada Ayah : Literatur Review - Nisa Aprilia; Hanifatur Rosyidah; Meilia Rahmawati (Syntax Corporation Indonesia, 2023)
Postpartum depression in fathers is currently receiving less attention compared to postpartum depression in mothers. Many studies primarily focus on postpartum depression in mothers. The prevalence of fathers experiencing postpartum depression is approximately 15.7% in the period after 1 year of childbirth compared to 3.6% in the period after 9 months postpartum. Several factors that predict the occurrence of postpartum depression in fathers include the relationship with their partners, lack of support from both family and friends, the pregnancy period, and sociodemographic factors (age, education, income). To examine several pieces of literature related to factors influencing the occurrence of Postpartum Depression in fathers. The method used in writing this article is a literature review found in health journal databases, such as PubMed. Articles selected are based on being full text, open access, and in the English language. A total of 158 articles were obtained, and out of those, 10 articles that met the criteria for factors influencing postpartum depression in fathers were available in full text and free access. Postpartum depression in fathers is a mental health disorder that cannot be ignored. Similar to postpartum depression in mothers, postpartum depression in fathers also needs special attention from healthcare professionals, family, partners, and the surrounding environment. In this regard, we will analyze several factors related to the causes and consequences of postpartum depression in fathers, as well as interventions that can be provided by healthcare professionals.